2004
DOI: 10.1109/tap.2004.827502
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Compensate for the Mutual Coupling Effect in an Adaptive Dipole Array

Abstract: A new method is introduced for the compensation of the mutual coupling effect of a linear adaptive dipole array employed in adaptive nulling of interference signals. The new method adopts a practical approach in that it needs only the measured voltages across the antenna terminal loads and an estimated current distribution for the calculation of the mutual impedances. The mutual impedance is defined and calculated differently from the conventional method and the results are more effective to remove the mutual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 12 publications
(27 reference statements)
4
73
0
Order By: Relevance
“…Case #1 shows the RMSE when the antenna is at h = 10λ, and we remove mutual coupling effects by using mutual impedance matrix measured over the same height. The RMSE is fairly low, which supports the applicability of the method presented in [21]. The critical situation is tested when the antenna is placed at h = 0.25λ, and the mutual impedance matrix is pre-estimated over h = 10λ, but surprisingly RMSE remains unchanged.…”
Section: Effects On Doa Estimationsupporting
confidence: 57%
“…Case #1 shows the RMSE when the antenna is at h = 10λ, and we remove mutual coupling effects by using mutual impedance matrix measured over the same height. The RMSE is fairly low, which supports the applicability of the method presented in [21]. The critical situation is tested when the antenna is placed at h = 0.25λ, and the mutual impedance matrix is pre-estimated over h = 10λ, but surprisingly RMSE remains unchanged.…”
Section: Effects On Doa Estimationsupporting
confidence: 57%
“…By definition, the conventional mutual impedance is the ratio of the induced open-circuit voltage of one antenna to the exciting terminal current of the other antenna [1]- [3]. However, some recent studies [4]- [6] have shown that the conventional definition of mutual impedance cannot accurately measure the mutual coupling effect. One of the deficiencies of the conventional mutual impedance lies in its failure to take into account the direction information of the receiving signals because of the requirement of one of the antenna elements in the transmitting mode whereas in a receiving array, all antenna elements are in the receiving mode, being excited by external source(s).…”
Section: Introductionmentioning
confidence: 99%
“…These three major differences substantiate the important extension to Carter's theory introduced in this paper. As already pointed out in [1,4] and [6][7][8], the concept of mutual impedances is inaccurate in estimating and compensating the effects of mutual coupling in receiving antenna arrays. The proposed MAIEM is therefore expected to yield superior performance to that of the open-circuit voltage method.…”
Section: The Multiple Antenna Induced Emf Methodsmentioning
confidence: 99%
“…For receiving antenna arrays, most of the available mutual coupling compensation methods [2,[5][6][7] are only usable over a limited range of frequencies since the accuracy of the coupling matrix varies with the frequency.…”
Section: Introductionmentioning
confidence: 99%